P.040 Moncton brain tumour tissue biorepository: diagnostic and therapeutic initiatives for glioma research in New Brunswick. (2nd June 2017) - Charest, V; Dao, T; Morin, P; Whitlock, P; Charest, D
Abstract : Background: Improving diagnostic and therapeutic tools associated with glioblastoma multiforme (GBM), an aggressive brain tumour, is crucial as average patient survival remains slightly over a year. Challenges include early diagnosis and acquired drug resistance. Improving these challenges notably require a multidisciplinary team and a dedicated brain tumour specimen collection initiative. We hypothesize that implementing such an approach in Moncton would provide significant benefits to GBM patients and researchers in New Brunswick.Methods: A Brain Tumour Tissue Repository was instigated to collect and preserve primary tumour specimens. Storage of circulating samples from patients undergoing temozolomide (TMZ) therapy was also performed. In parallel, molecular leads were investigated in different GBM models to identify therapeutic targets.Results: Collection of 7 primary specimens was accomplished in 2016. Over 15 primary samples are housed in the tumour biorepository to date with circulating samples collected from 3 patients. Additionally, numerous deregulated non-coding RNAs were identified by qRT-PCR in GBM models and shown to be modulated following TMZ treatment warranting further investigation.Conclusions: Overall, these results provide novel therapeutic leads for GBMs and, most importantly, highlight the instigation of a New Brunswick-based brain tumor biorepository which will undoubtedly strengthen brain tumour research in the Maritimes.